2019
DOI: 10.1113/jp278073
|View full text |Cite
|
Sign up to set email alerts
|

UBR5 is a novel E3 ubiquitin ligase involved in skeletal muscle hypertrophy and recovery from atrophy

Abstract: Key points We have recently identified that a HECT domain E3 ubiquitin ligase, named UBR5, is altered epigenetically (via DNA methylation) after human skeletal muscle hypertrophy, where its gene expression is positively correlated with increasing lean leg mass after training and retraining. In the present study we extensively investigate this novel and uncharacterised E3 ubiquitin ligase (UBR5) in skeletal muscle atrophy, recovery from atrophy and injury, anabolism and hypertrophy. We demonstrated that UBR5 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 79 publications
11
68
1
Order By: Relevance
“…Thus, this supports the idea that UPP acts as a negative regulator of muscle hypertrophy under the influence of MAFbx and MuRF1, but promotes muscle hypertrophy with other proteins regulating UPP. It is worth noting that a recent study has found another E3 ligase, UBR5, with gene expression and protein levels increasing during periods of muscle recovery following muscle atrophy and seemed to be regulated inversely compared to MAFbx and MuRF1 during functional overloading in rats . Furthermore, UBR5 expression was found to be positively associated with muscle loading in untrained male subjects .…”
Section: The Mammalian Target Of Rapamycin (Mtor)/protein Kinase B (Amentioning
confidence: 80%
“…Thus, this supports the idea that UPP acts as a negative regulator of muscle hypertrophy under the influence of MAFbx and MuRF1, but promotes muscle hypertrophy with other proteins regulating UPP. It is worth noting that a recent study has found another E3 ligase, UBR5, with gene expression and protein levels increasing during periods of muscle recovery following muscle atrophy and seemed to be regulated inversely compared to MAFbx and MuRF1 during functional overloading in rats . Furthermore, UBR5 expression was found to be positively associated with muscle loading in untrained male subjects .…”
Section: The Mammalian Target Of Rapamycin (Mtor)/protein Kinase B (Amentioning
confidence: 80%
“…In comparison, MuRF1 and MAFbx expression remain elevated for a longer time period in neurogenic muscle atrophy models, returning to baseline after 14 days. (9,12,16,22,35). Thus, we hypothesized that Fbxl22 could be involved in the early initiation of the muscle atrophy process.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of mouse skeletal muscle with plasmid DNA was performed in mice under isoflurane (2-4% inhalation) anesthesia as previously described (12,64). Briefly, after a 2hr pre-treatment with 0.4 units/µl of bovine placental hyaluronidase (Sigma) resuspended in sterile 0.9% saline, 20µg of plasmid DNA was injected into either the tibialis anterior (TA) or the lateral and medial gastrocnemius muscles (lateral gastrocnemius, LGA; medial gastrocnemius, MGA).…”
Section: In Vivo Electroporationmentioning
confidence: 99%
See 2 more Smart Citations